2018
DOI: 10.1186/s13058-018-0969-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia-inducing antipsychotics increase breast cancer risk by activating JAK-STAT5 in precancerous lesions

Abstract: BackgroundPsychiatric medications are widely prescribed in the USA. Many antipsychotics cause serum hyperprolactinemia as an adverse side effect; prolactin-Janus kinase 2 (JAK2)-signal transducer and activator of transcription 5 (STAT5) signaling both induces cell differentiation and suppresses apoptosis. It is controversial whether these antipsychotics increase breast cancer risk.MethodsWe investigated the impact of several antipsychotics on mammary tumorigenesis initiated by retrovirus-mediated delivery of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 68 publications
2
48
0
Order By: Relevance
“…Data from Giordano et al [30] illustrated that the changes of the JAK/STAT5 signaling pathways in colorectal cancer can improve the therapeutic effects mediated by LY6G6D. Recent work by Johnston et al [31] has established that psychotropic drugs can increase the risk of breast cancer by activating the JAK/STAT5 signaling pathways in precancerous lesions. Moreover, studies of Lopez et al [32] showed the importance of JAK/STAT5 in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Giordano et al [30] illustrated that the changes of the JAK/STAT5 signaling pathways in colorectal cancer can improve the therapeutic effects mediated by LY6G6D. Recent work by Johnston et al [31] has established that psychotropic drugs can increase the risk of breast cancer by activating the JAK/STAT5 signaling pathways in precancerous lesions. Moreover, studies of Lopez et al [32] showed the importance of JAK/STAT5 in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mibefradil has been recently reapproved, under the condition of "orphan medication," so that its efficacy for the treatment of pancreatic cancer, glioblastoma multiforme, and ovarian cancer can be investigated (clinicaltrials.gov). Similarly, Pimozide-an antipsychotic drug-is also a strong inhibitor of TTCCs that inhibits tumor cell proliferation and decreases cell migration in hepatocellular carcinoma [51], prostate cancer [52], breast cancer [53], and melanoma [54]. Consequently, the inhibition of TTCCs affects their functionality; therefore, the cellular functions involved are compromised.…”
Section: Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Evidence supports the possible increased risk of breast cancer in women with schizophrenia due partly to the use of antipsychotic medications [29], some of which may cause hyperprolactinaemia, which, in turn, may contribute to mammary development and breast carcinogenesis in animal and cell experiments [30,31]. Johnston et al found that two hyperprolactinemia-inducing antipsychotics, risperidone and pimozide, incite precancerous cells to progress to cancer by activating JAK-STAT5 signaling [32]. Patients with schizophrenia show decreased incidence of prostate cancer [25,33], which is theoretically related to low testosterone levels suppressed by high prolactin levels on account of antipsychotic drug use [34].…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%